2007
DOI: 10.1002/masy.200750111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morphology on the Relaxation Processes and Mechanical Properties in Polyimide/Silica Hybrids

Abstract: Polyimide/silica hybrids were produced by a sol‐gel process and were examined in terms of their morphology, dynamic‐mechanical properties and mechanical performances. Two types of morphology were obtained by tailoring the composition of the precursor solution mixture, i.e. phase‐ separated or co‐continuous systems. These morphologies were found to exhibit considerably different properties. In particular, co‐continuous nanocomposite systems were found much more effective in suppressing molecular relaxation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…For a silica concentration of 22.3 wt%, calculated theoretically assuming complete conversion of TEOS and GOTMS to silica [33], the threshold GOTM/TEOS molar ratio is located between 0.06 and 0.08. Figure 4 shows the SEM micrographs of hybrids having 22.3 wt% of silica and GOTMS contents below and above the threshold value [32]. For GOTMS concentrations lower than the limiting value, the hybrids display (Figures 4a and 4b) a particulate morphology like that of Figures 3a, but with smaller particles sizes.…”
Section: Processing and Morphologymentioning
confidence: 95%
See 3 more Smart Citations
“…For a silica concentration of 22.3 wt%, calculated theoretically assuming complete conversion of TEOS and GOTMS to silica [33], the threshold GOTM/TEOS molar ratio is located between 0.06 and 0.08. Figure 4 shows the SEM micrographs of hybrids having 22.3 wt% of silica and GOTMS contents below and above the threshold value [32]. For GOTMS concentrations lower than the limiting value, the hybrids display (Figures 4a and 4b) a particulate morphology like that of Figures 3a, but with smaller particles sizes.…”
Section: Processing and Morphologymentioning
confidence: 95%
“…These interactions delay the onset of phase separation by spinodal decomposition, which results in a higher viscosity of the solution and in a reduction of the rate of particle growth [5,8,32]. It was found that a threshold value of the GOTMS/TEOS molar ratio exists for the formation of co-continuous morphologies [8,32]. This threshold value was found to change with the overall silica content in the hybrid.…”
Section: Processing and Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…where A is the pre-exponential factor, R is the gas constant, T is the absolute peak temperature, and E a is the activation energy for the relaxation process [26]. E a represents the relationship between the mechanical loss factor and temperature.…”
Section: Thermomechanical Propertiesmentioning
confidence: 99%